2015
DOI: 10.1007/s11682-015-9392-6
|View full text |Cite
|
Sign up to set email alerts
|

Dyslexia and language impairment associated genetic markers influence cortical thickness and white matter in typically developing children

Abstract: Dyslexia and language impairment (LI) are complex traits with substantial genetic components. We recently completed an association scan of the DYX2 locus, where we observed associations of markers in DCDC2, KIAA0319, ACOT13, and FAM65B with reading-, language-, and IQ-related traits. Additionally, the effects of reading-associated DYX3 markers were recently characterized using structural neuroimaging techniques. Here, we assessed the neuroimaging implications of associated DYX2 and DYX3 markers, using cortical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 63 publications
0
22
0
Order By: Relevance
“…An association between white matter volume in the left temporo‐parietal region and KIAA0319 SNP rs6935076 has been identified (Darki et al, ) and replicated with an additional right hemisphere effect when data from a third longitudinal time point were added to the analysis (Darki et al, ). Furthermore, Eicher et al () reported decreased cortical thickness in a left orbitofrontal region in carriers of the minor allele of the SNP rs9461045 (associated with single‐word reading and spelling ability; Dennis et al, ) relative to those homozygous for the major allele within a sample of individuals ages 3–20 years from the Pediatrics Imaging Neurocognition Genetics study (PING) database . With regard to structural connectivity, the minor allele of the same SNP was associated with reduced white matter integrity in the corpus callosum.…”
Section: Specific Reading Disabilitymentioning
confidence: 99%
See 2 more Smart Citations
“…An association between white matter volume in the left temporo‐parietal region and KIAA0319 SNP rs6935076 has been identified (Darki et al, ) and replicated with an additional right hemisphere effect when data from a third longitudinal time point were added to the analysis (Darki et al, ). Furthermore, Eicher et al () reported decreased cortical thickness in a left orbitofrontal region in carriers of the minor allele of the SNP rs9461045 (associated with single‐word reading and spelling ability; Dennis et al, ) relative to those homozygous for the major allele within a sample of individuals ages 3–20 years from the Pediatrics Imaging Neurocognition Genetics study (PING) database . With regard to structural connectivity, the minor allele of the same SNP was associated with reduced white matter integrity in the corpus callosum.…”
Section: Specific Reading Disabilitymentioning
confidence: 99%
“…In addition to DCDC2 and KIAA0319 , two additional genes within 6p22‐21.3 ( THEM2 and NRSN1 ) have been linked with reading ‐ associated neural structure and/or function across multiple studies. Presence of the minor allele at rs3777663 in THEM2 (also known as ACOT13 and previously identified as a protective allele [Eicher et al, ]) has been linked to increased cortical thickness in the left inferior frontal region (Eicher et al, ). In a separate study, Pinel et al () found that THEM2 SNP rs17243157 was associated with functional asymmetry in a posterior temporal region during reading and speech listening tasks, with a stronger effect for reading.…”
Section: Specific Reading Disabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…This questionnaire assessed medical, developmental, and behavioral history of participants, in addition to the family history of medication, alcohol problems, and so on. The cognitive assessment was conducted using NIH Toolbox Cognition Battery [32]. This toolbox consisted of tests measuring executive functions, language, and attention (for a complete detailed discussion on all of the collected behavioral measures, see [33]).…”
Section: Methodsmentioning
confidence: 99%
“…PING DTI imaging techniques, data acquisition, and analyses are discussed briefly below. In-depth descriptions can be found elsewhere (Eicher et al, 2013(Eicher et al, , 2015Fjell et al, 2012).…”
Section: Diffusion Tensor Imagingmentioning
confidence: 99%